The multidimensional landscape of pharmacovigilance: introduction and history - Hagemann, Ulrich (Henry Stewart Talks, 2023)
Pharmacovigilance (PV), Pharmacotherapy, Reasons for knowledge deficits in clinical trials, Pharmacovigilance and public health, Clinical medicine and expertise